2021
DOI: 10.3390/ijerph18126204
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence during the COVID-19 Pandemic: A Review of the Phenomenon from Victims’ and Help Professionals’ Perspectives

Abstract: Social isolation is considered one of the main risk factors leading to intimate partner violence episodes; this evidence also emerged during the application of stay-at-home policies to contain the COVID-19 pandemic. For this reason, we aimed to collect data on intimate partner violence over the last year, comparing data reported by victims with data collected by help professionals. In accordance with PRISMA guidelines, through keywords related to abuse, pandemic and containment measures, 3174 articles were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 63 publications
4
45
0
1
Order By: Relevance
“…In line with the growing literature assessing the link between the COVID-19 pandemic and IPV [ 5 , 6 , 8 , 9 ], intimate partner violence in Norway, as reported to the police, increased substantially during lockdown compared to the pre-lockdown period. Similar results has been found in previous studies on intimate partner violence during the COVID-19 pandemic [ 9 ]. Furthermore, during lockdown the police assessed the cases as being at higher risk for imminent and severe violence.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In line with the growing literature assessing the link between the COVID-19 pandemic and IPV [ 5 , 6 , 8 , 9 ], intimate partner violence in Norway, as reported to the police, increased substantially during lockdown compared to the pre-lockdown period. Similar results has been found in previous studies on intimate partner violence during the COVID-19 pandemic [ 9 ]. Furthermore, during lockdown the police assessed the cases as being at higher risk for imminent and severe violence.…”
Section: Discussionmentioning
confidence: 68%
“…Although there is little scientific knowledge about the consequences of the COVID-19 pandemic on family violence, there are indications that social distancing and lockdowns of societies have increased family conflicts [ 8 , 9 ]. A recent systematic review and meta-analysis of 18 studies from countries around the world excluding Norway, found that intimate partner violence had increased after COVID-19 lockdowns (mean effect size 0.66, CI = 0.08–1.24) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intimate partner violence (IPV) is a heterogeneous construct that includes several forms of violence—physical, sexual, economic, psychological/emotional, stalking—perpetrated by an intimate partner [ 1 , 2 , 3 ]. Although the reported prevalence of IPV varies considerably across studies [ 4 , 5 , 6 , 7 , 8 , 9 ], the findings are in agreement that the prevalence of the emotional/psychological form of violence is higher (5–91%) [ 5 , 6 , 7 , 10 ] than the physical/sexual form (3–59%) [ 5 , 6 , 7 , 11 , 12 ]. Psychological violence in IPV is frequently experienced in conjunction with other forms of violence, but can also occur alone and precede, or represent an important risk factor for physical/sexual violence [ 2 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 59%
“…The results from the 2019 data showed the presence of the children as the only predictor of domestic violence; while the type of relationship and the weapon seemed to be predictive factors on the data collected during the Italian lockdown. The narrative and detail selection in the newspapers is certainly a factor to be taken into account, but it can also be hypothesized that the type of relationship (IPV or DV) seems to play a more important role during the lockdown phase: a lack of social support, forced cohabitation, are all factors that may increase the perceived stress [44] and, consequently, may have led to the exacerbation of violent situations [15].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation as a strategy for pandemic management can become an important risk factor for IPV, as it happened during the spread of a new strain of Coronavirus and its associated disease . Lockdown measures like being forced to stay at home 24 h a day with your partner or other family members significantly increases the likelihood of episodes of home-based violence and is accompanied by a limited possibility of complaints or defense by the victim [13][14][15]. Italy, from 9 March 2020 up to the 18 May 2020, enacted several highly restrictive decrees, initially limited to some areas and then extending to the whole country and lasting for three months.…”
Section: Introductionmentioning
confidence: 99%